Hands-On Artificial Intelligence on Google Cloud Platform : Build intelligent applications powered by TensorFlow, Cloud AutoML, BigQuery, and Dialogflow /: Build intelligent applications powered by TensorFlow, Cloud AutoML, BigQuery, and Dialogflow. (2020) - Deshpande, Anand; Kumar, Manish; Chaudhari, Vikram
No abstract available